An investigation of mental health care pathways for patients with psychosis who engage in antisocial behaviours - Challinor, Alexander (The journal of forensic psychiatry & psychology, 2023)
Secure mental health services aim to assess and treat mentally disordered offenders, where a patients care pathway involves their movement from service to service on an individual journey towards recovery. Research has attempted to understand the relationship between psychosis and violence for mentally disordered offenders. From this empirical evidence base a tripartite typology has emerged. Three subgroups have been categorised as (i) schizophrenia preceded by conduct disorder (SZ+CD), (ii) offenders with schizophrenia who begin offending at illness onset (SZ+AS), and (iii) offenders with schizophrenia (SZ). This study aimed to examine differences in care pathways between subgroups. The sample consisted of 77 male patients admitted to low- and medium-secure care. The subgroup of patients was determined from data collected from health records. The analysis examined the differences in patient care pathways. The results demonstrated differences in subgroup pathways to, within and from secure services. The SZ+CD subgroup had a higher number of placements used, were more likely to transition between the same level of security, and had an increased use of the private sector. The SZ+AS subgroup was significantly more likely to use intensive care and less likely to use high secure services. Examining care pathways of mentally disordered offenders will ensure a more evidence-based approach to the configuration and operationalisation of services, help guide policymakers and hopefully improve patient care.